Size variation and body proportions in an isolated Holocene-aged population of Hominids from Palau, Micronesia and its impact on our understanding of variation in extinct Hominids. - De Klerk, Bonita (My University, 2013)
This thesis investigated whether a fragmented assemblage of fossilized Homo sapiens remains collected from Palau; Micronesia represents a population exhibiting a case of insular dwarfing. The earliest occupation of Palau is ca. 4000 YBP, and the fossil assemblage studied here dates between 2900 – 1400 YBP, thus providing a relatively short time in which body size reduction, due to insular dwarfism could occur. There are well known cases, in both the modern and fossil context, where insular dwarfism and body size reduction is known to occur in human populations that are isolated, but the results of this reduction are seen over a much longer period (e.g., tens of thousands of years). Metric dimensions of the humerus, radius, ulna, femur, tibia, and fibula and os coxa are quantified in order to evaluate other potential insular dwarfs in fossil hominin assemblages, such as Homo floresiensis. Previous studies have shown that the Palau archipelago has remained relatively isolated from human contact due to the surrounding currents, providing ideal conditions for insular dwarfism to occur. Comparing measurements taken on populations encompassing a reasonable range of human variation, this study quantified and compared the Palauan measurements and joint ratios to determine which variables might differentiate among these population groups, thus indicating traits potentially uniquely signalling a reduction in human body size. Disproportionate joint sizes were observed in the humerus, ulna, tibia, and femur of the Palauan sample. While individual measurements from the Palau sample all fall comfortably within the range of measurements taken from other small-bodied human individuals, the articular surfaces of Palauan specimens do not resemble those from other well-established, small-bodied insular populations. As the articular surfaces are smaller relative to the epiphyseal diameters and may be a reflection of the relatively short time in which the reduction has taken place. Morphologically the Palauan population exhibits small orbits, a large interorbital distance, an inflated glabella region and protruding supraorbital tori. A reduction in the mandible may account for the overcrowding of teeth observed in the dentition. The Palauan individuals have disproportionately large maxillary teeth. The mandibular dentition, however, varies: the incisors, canine and first molars are large, while reduction is seen most easily in the premolars and the second molar. This dental reduction is coupled with significant differences between the cervico-enamel junctions for these teeth and the corresponding crown measurements. Large teeth, inflated glabella, and protruding supraorbital tori may be an indication of a founding population. These traits are all found in Australomelanesian populations, and it is thus possible that the Palauan population under study originated from Melanesia (e.g. New Guinea or South East Asia). Application of the present study to Homo floresiensis, a fossil hominin suggested by some authors to have undergone insular dwarfing, reveals that while H. floresiensis is small for some measurements, most fall within the range of the small-bodied comparative sample from Palau. The stature of H. floresiensis is not unusually small and falls within the ranges of the comparative sample used here. The only comparison that can be made for joint size is that both the Palauan and H. floresiensis femoral heads are small and both exhibit the same disproportionate dimensions of the proximal tibia. As potential body size reduction is possibly responsible for the Palauan traits, the similarity in joint proportions may be attributed to insular dwarfing when the population first became isolated, as these joint irregularities are not seen in established insular dwarfs (Andaman and Nicobarese). The differences present in the measurements obtained for all the small-bodied samples examined suggests that even though insular populations may present as small-bodied, the island populations (fossil or extant) should be viewed as a case by case study. Isolation, life history, founding population (genetics) and environmental conditions all affect population body size over time, but to assume that all isolated populations will decrease body size in the same way is incorrect. What is seen in Palauan specimens is likely the adaptive responses of a isolated population from Melanesia, resulting in the insular dwarfism observed. By examining the available aspects of this insular population and found that it was consistent in reflecting size and proportions of small-bodied populations.
Keywords: Hominids - Palau.; Human beings.; Palaentology - Holocene.